Antigen-Specific CD4+CD8+ Double-Positive T Cells Are Increased in the Blood and Spleen During Ehrlichia chaffeensis Infection in the Canine Host - McGill, Jodi L.; Wang, Ying; Ganta, Chanran K.; Boorgula, Gunavanthi D. Y.; Ganta, Roman R. (Frontiers in Immunology, 2018)
Ehrlichia chaffeensis is an obligate intracellular bacterium belonging to the order, Rickettsiales and is a frequent cause of severe and fatal tick-borne infection in people in North America. The reservoir host for E. chaffeensis is the white-tailed deer, while humans and dogs are regarded as common incidental hosts. In dogs, we and others have shown that E. chaffeensis establishes a chronic infection that persists for several weeks to months, while promoting the development of Th1 and Th17 cellular responses and pathogen-specific humoral immunity. We demonstrate here that vaccination with a live, attenuated clone of E. chaffeensis bearing a targeted mutation in the Ech_0230 gene neither promotes the development of long-lived cellular or humoral immunity, nor confers protection against secondary wild-type E. chaffeensis challenge. In dogs, a population of mature CD4+CD8+ double-positive (DP) T cells exists in the periphery that shares similarities with the DP T cell populations that have been described in humans and swine. Little is known about the function of these cells, particularly in the context of infectious diseases. Here, we demonstrate that canine DP T cells expand significantly in response to E. chaffeensis infection. Using in vitro antigen recall assays, we further demonstrate that canine DP T cells undergo clonal expansion, produce IFNγ and IL-17, and upregulate expression of granzyme B and granulysin. Together, our results demonstrate that DP T cells accumulate in the host during E. chaffeensis infection, and suggest that alternative lymphocyte populations may participate in the immune response to tick-borne infections in the incidental host.